Pemanfaatan Karaginan Untuk Membuat Permen Jelly Jamu Cekok - Hidayati, Sri; Tumanggor, Hotma Ria; Nurainy, Fibra; koesoemawardani, Dyah (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
Herbal medicine is a local wisdom that is used by some Indonesian people to treat children who lack appetite. The bitter taste is not liked by children, so efforts are needed to reduce the bitter taste and make jamu cekok liked by children by making it into candy. One of the ingredients that can be used to make jelly candy is carrageenan. The purpose of this study was to obtain the best concentration of carrageenan with sensory and chemical properties that were sensory-preferred and SNI 3547.2-2008. The results showed that the best carrageenan concentration was the addition of 14% carrageenan, which resulted in jamu Cekok jelly candy with a color score of 3.15 (slightly brownish red), aroma 3.50 (slightly typical of herbal medicine), texture 4.41 (chewy), taste 4. .34 (not bitter), overall acceptance was 4.31 (liked), water content was 9.88%, ash content was 1.59%, pH was 4.55, reducing sugar was 9.29%. All observation variables have met the SNI standard for water content, ash content and reducing sugar